Gender Participation in the Management of MT. Calavite Wildlife Sanctuary and Mt. Arayat Protected Landscape in the Philippines - GUTIERREZ, Jonnel; ESCULTOR, Aida D. L.; CRUZ, Moesa C. Dela; CORTADO, Jay Mark G. (PT Keberlanjutan Strategis Indonesia, 2025)
This study examines the gender responsiveness of management practices in two Protected Areas (PAs) in Luzon, Philippines: Mt. Calavite Wildlife Sanctuary (MCWS) and Mt. Arayat Protected Landscape (MAPL). Using a descriptive-quantitative approach, data were gathered through surveys and external assessments to evaluate the gender sensitivity of Protected Area Management Plans (PAMPs), staff composition, and gender-related initiatives. Findings reveal that although both PAs are rated as gender-aware in their PAMPs, gender imbalances persist in staffing, particularly in roles such as Forest Rangers, Information Officers, and Forest Attendants, which are occupied exclusively by one gender. Operational gaps were noted despite gender-responsive plans, especially in MAPL, where some staff believe men are not adequately informed about Republic Act No. 9710 (Magna Carta of Women), indicating a need for training. Funding limitations were also found to hinder the implementation of women-empowerment programs. The study recommends developing policies to eliminate gender bias in job assignments and promoting equal participation of all genders in PA management. Bridging the gap between planning and practice is essential to achieving inclusive, equitable, and sustainable conservation outcomes.